Multiple uses of common pool resources in semi-arid West Africa: A survey of existing practices and options for sustainable resource management - Williams, Timothy O. (International Food Policy Research Institute, 1997)
Common pool resources such as rangeland, forests, fallow fields, and ponds provide an array of social and economic benefits for a wide variety of users in semi-arid West Africa. However, poor definition and enforcement of the institutional arrangements governing the use of these resources sometimes lead to social conflicts and resource degradation. This problem arises partly due to the multiple functions and temporal variability of common pool resources and partly due to the heterogeneity and overlapping rights of users. These features and increasing concerns about the future productive capacity of the natural resource base raise important questions concerning the choice of institutions most likely to promote sustainable management of common pool resources. This paper presents evidence from field studies on the current status, use and management of multi-product, common pool resources in semi-arid West Africa. The evidence suggests that the large number of heterogenous users and the multiple functions of these resources permit an intensive use of land and serve to minimize production risk. The divergent interests and preferences of various user groups, however, need to be reconciled to prevent resource degradation. The paper provides guidelines on institutional arrangements and policy measures to promote improved management of common pool resources in semi-arid West Africa and other areas with similar agro-ecological conditions.